The Effect of Profitability, Capital Structure, Company Size, and Dividend Policy on Company Value on the Indonesia Stock Exchange - Titik Purwanti (STIE AAS Surakarta, 2020)
Every company, especially companies that have gone public have value. The value that is owned by the company is a perception that comes from investors to the level of achievement of the success of a company in managing various resources that are controlled and owned which is reflected in the stock price of the company in the market. This study aims to determine the effect of profitability, capital structure, company size, and dividend policy on firm value. The companies in this study are manufacturing companies listed on the Indonesian stock exchange during the period of 2015 to 2018. The population of this research is all manufacturing companies listed on the Indonesian stock exchange in 2015-2018. The research sample of 11 companies. The technique used in the sampling of this study used a purposive sampling technique. In this study secondary data was obtained from the Indonesian Capital Market Directory. Data analysis techniques using descriptive statistics and testing using the classic assumption test. Testing the research hypothesis using multiple linear regression test, simultaneous test (F test), partial test (t test), and coefficient of determination test (R2 test). The results showed that simultaneous profitability, capital structure, company size, and dividend policy significantly influence the value of manufacturing companies. Partially, profitability has a positive and significant effect on firm value, capital structure has a positive and significant effect on firm value, company size has a negative and significant effect on firm value, and dividend policy has positive and not significant effect on firm value.